The stranger in early modern and modern Jewish tradition - Bartlett, Catherine, 1967-; Schlör, Joachim, 1960- (Leiden ; Boston : Brill, 2021)
"Angels are the ultimate stranger. They come from another world and have a special place in the art of the Russian Jewish painter Marc Chagall (1887-1985). In My Life (1923) the young Chagall recalls one memorable night in Saint-Petersburg. Drifting into sleep in the corner of a room (all he could afford) he suddenly saw the ceiling open and a winged being, surrounded by light and blue air, hovered above him before disappearing through the ceiling again"--
Copyright / Editors: Catherine Bartlett and Joachim Schlör -- Notes on Contributors / Editors: Catherine Bartlett and Joachim Schlör -- Chapter 1 Introduction / Author: Catherine Bartlett -- Chapter 2 "The Penitents" / Author: Eyal Davidson -- Chapter 3 The African Hebrew Israelites of Jerusalem / Author: Michael T. Miller -- Chapter 4 Rights of the Stranger in Jewish Moral / Author: Mathias Berek -- Chapter 5 The Origins of the Stranger / Author: Søren Blak Hjortshøj -- Chapter 6 The Jewish Stranger in Germany and America / Author: Chad Alan Goldberg -- Chapter 7 (Friendly) Strangers in Their Own Land No More / Author: Dani Kranz -- Chapter 8 "They Are Not My People" / Author: Federico Dal Bo -- Chapter 9 Between Language and Ethnicity / Author: Olga Tabachnikova -- Chapter 10 Jews as Strangers, Strangers as Jews in the Twentieth-Century French Novel / Author: Maxime Decout -- Chapter 11 Exorcizing the Stranger / Author: Efraim Sicher -- Chapter 12 Muslims as Brothers or Strangers? French Jewish Thinkers Confront the Moral Dilemmas of the French-Algerian War / Author: Ethan B. Katz -- Chapter 13 The Christian Orphan as the Stranger in Nineteenth-Century European Jewish Fiction / Author: Catherine Bartlett -- Chapter 14 The Strange Face and Form of the Stranger in Levinas / Author: Benda Hofmeyr -- Chapter 15 Conclusion: Jews and Strangers. Perspective from History / Author: Joachim Schlör -- Index / Editors: Catherine Bartlett and Joachim Schlör.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 23, 2021).
eBooks on EBSCOhost
Keywords: Other (Philosophy) -- Religious aspects; Strangers -- Religious aspects -- Judaism; Étrangers -- Aspect religieux -- Judaïsme.; Other (Philosophy) -- Religious aspects; Strangers -- Religious aspects -- Judaism